Different roads to the same destination – The impact of impulsivity on decision-making processes under risk within a rewarding context in a healthy male sample. (28th February 2016) - Dinu-Biringer, Ramona; Nees, Frauke; Falquez, Rosalux; Berger, Moritz; Barnow, Sven
Abstract: The results of research about the influences of impulsivity on decision-making in situations of risk have been inconsistent. In this study, we used functional magnetic resonance imaging to examine the neural correlates of decision-making under risk in 12 impulsive, as defined by the Barratt Impulsiveness Scale-11, and 13 normal men. Although both groups showed similar decision-making behavior, neural activation regarding decision-making processes differed significantly. Impulsive persons revealed stronger activation in the (ventro-) medial prefrontal cortex and less deactivation of the orbitofrontal cortex while playing for potential gains. These brain regions might be associated with the emotional components of decision-making processes. Significant differences in brain areas linked to cognitive decision-making components were not found. This activation pattern might be seen as an indication for a hypersensitivity to rewarding cues in impulsive persons and might be linked to the propensity for inappropriate risk-taking behavior in persons with more extreme impulsivity levels, especially in situations in which they have a strong emotional involvement in the decision process. Highlights: We investigated the influence of impulsivity on decision-making under risk. We distinguished between decisions for reward and for avoiding punishment. Groups showed a similar decision-making behavior but neural activation differed. Impulsive people showed higher activation in the vmPFC/less deactivation of the OFC. A hypersensitivity to rewarding stimuli in impulsive persons is supposed.